Micaela magazine, an experience of Latin American women in exile - Bloch, Martina (Área Feminismos, Género y Sexualidades del Centro de Investigaciones "María Saleme de Burnichón" de la Facultad de Filosofía y Humanidades, Universidad Nacional de Córdoba, 2021)
As part of an ongoing research project on the memories of feminism in the 1980s in Argentina, we present an approach to the experience of the magazine Micaela, published in Sweden by the Latin American Women's Association (ALAM) between 1978 and 1993. In the pages of Micaela, in addition to its own articles, ALAM published the information it received from correspondents established in countries that provided asylum to Latin American refugees. Through interviews, publications of meetings and activities, useful information for exiles in Sweden, reflections on Latin American women, on feminism or on issues that affected them as women -abortion, family, sexuality, role in struggles and militancy, to mention a few-, the articles in Micaela magazine vindicated the role of women in the struggle for social justice. We will analyse Micaela's articles in three categories: "We Women", "Practical Information for Exiles" and "Latin American Political Situation"; which will allow us to approach the concerns of Latin American women exiled in Sweden.